Didactical design of algebraic expression from a linear pattern with a realistic mathematics education approach - Fitriani, Nur; Sugiman, Sugiman; Arfah, Arfah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2023)
The design of didactic mathematics learning is designed by taking into account the learning barriers of students. This study aims to obtain a didactic design for learning algebraic expression from a linear pattern to reduce student learning barriers through the application of Realistic Mathematics Education (RME). The type of this research is design research with three stages, namely the plan, do, and see. The research data was in the form of qualitative data with the research instruments used were Hypothetical Learning Trajectory (HLT)on algebraic forms of linear patterns, student worksheet, pretest and posttest, observation sheets, teacher interview sheets, and student interview sheets which were then analyzed retrospectively. This research constructs a didactic design in the form of a learning trajectory divided into nine stages and packaged in four activities. The applied didactic design opens the thinking process for students to find the meaning of variables and algebraic forms of the mathematical activities themselves. This didactical design is proven to reduce students' learning obstacles.